Illocutionary Speech Act Analysis in the Nightbooks Movie - Hosiaa Hosiaa; Ayu Oktaviani; Yulfi Yulfi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research analyzes the types of illocutionary acts. Therefore, the problem of this research is